Respuesta :
Answer:
The correct answer is x = 3 and y = 2.
Step-by-step explanation:
There are many ways to solve systems of equations like this, but I'm going to use substitution. This means taking the value of y given by the second equation and plugging it into the first equation. This is modeled below:
2x - y = 4
2x - (-2x+8) = 4
Now, we can simplify the left side of the equation.
2x + 2x - 8 = 4
4x - 8 = 4
We should add 8 to both sides as the next step.
4x = 12
Now we can divide by 4.
x = 3
To solve for y, we can substitute this value found for x back into either one of our original equations.
y = -2x + 8
y = (-2*3) + 8
y = -6 + 8
y = 2
Therefore, the correct answer is x = 3 and y = 2.
Hope this helps!
Answer:
The value of x is 3 and y is 2
Step-by-step explanation:
Here, 2x - y = 4 and y = -2x + 8 are two given equation,
Now, We will use Substitution Method
2x - y = 4 ...(1)
y = -2x + 8 ...(2)
Substitute the value of y = -2x + 8 in equation (1)
2x - y = 4
2x - (-2x + 8) = 4
2x + 2x - 8 = 4
4x - 8 = 4
Add 8 both side we get,
4x - 8 + 8 = 4 + 8
4x = 12
Divide by 4 both side we get,
4x/4 = 12/4
x = 3
Now, Substitute the value of x in equation (2)
y = -2x + 8
y = -2(3) + 8
y -6 + 8
y = 2
Thus, The value of x is 3 and y is 2
FOR VERIFICATION ONLY:
2x - y = 4
2(3) - (2) = 4
6 - 2 = 4
4 = 4
y = -2x + 8
2 = -2(3) + 8
2 = -6 + 8
2 = 2
Hence, L.H.S = R.H.S
-TheUnknownScientist